2013
DOI: 10.1038/npp.2013.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conditional Central Expression of HIV-1 Tat Protein to Potentiate Cocaine-Mediated Psychostimulation and Reward Among Male Mice

Abstract: As a major neuropathogenic factor associated with human immunodeficiency virus (HIV) infection, HIV-1 Tat protein is known to synergize with psychostimulant drugs of abuse to cause neurotoxicity and exacerbate the progression of central nervous system pathology. However, the functional consequences of the interaction between HIV-1 Tat and abused drugs on behavior are little known. We tested the hypothesis that HIV-1 Tat expression in brain would modulate the psychostimulant effects of cocaine. Using the GT-tg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 48 publications
9
71
0
Order By: Relevance
“…The expression of Tat 1–86 protein in the GT-tg brain is dependent on the dose- and duration of doxycycline treatment (Carey et al, 2012; Paris et al, 2013). Tat expression in this model recapitulates clinical findings of HIV characterized by central macrophage/monocyte infiltration, T-lymphocyte infiltration, neuronal cell death (Kim et al, 2003), as well as dose-dependent reductions in limbic gray matter density (Carey et al, 2013), reductions in cognitive performance (Carey et al, 2012), increased anxietylike responding among males (Paris et al, 2013), and enhancement of psychostimulant reward (Paris et al, 2014). …”
Section: Methodsmentioning
confidence: 61%
“…The expression of Tat 1–86 protein in the GT-tg brain is dependent on the dose- and duration of doxycycline treatment (Carey et al, 2012; Paris et al, 2013). Tat expression in this model recapitulates clinical findings of HIV characterized by central macrophage/monocyte infiltration, T-lymphocyte infiltration, neuronal cell death (Kim et al, 2003), as well as dose-dependent reductions in limbic gray matter density (Carey et al, 2013), reductions in cognitive performance (Carey et al, 2012), increased anxietylike responding among males (Paris et al, 2013), and enhancement of psychostimulant reward (Paris et al, 2014). …”
Section: Methodsmentioning
confidence: 61%
“…TAT expression has been shown to increase the rewarding effects of methamphetamine (Kesby et al 2016b), ethanol (McLaughlin et al 2015) and cocaine (Paris et al 2014c). However, the effects of TAT exposure on psychostimulant-induced locomotor sensitization are mixed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of TAT exposure on psychostimulant-induced locomotor sensitization are mixed. For example, TAT−expressing mice and rats with intra-Acb TAT injections show an increased locomotor response to acute cocaine (Harrod et al 2008; Paris et al 2014c). However, intra-Acb injections of TAT before or after acquisition of cocaine sensitization have been shown to decrease sensitized locomotor responses (Ferris et al 2010; Harrod et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using transgenic mice with an inducible Tat gene, McLaughlin and colleagues revealed that cocaine-induced hyperlocomotion and conditioned place preference were enhanced with brain expression of Tat (Paris et al 2014). Conditioned place preference is an associative learning task that provides an indirect measure of the cocaine-mediated reward.…”
Section: Discussionmentioning
confidence: 99%